STRATEGI GURU DALAM MENINGKATKAN KEMAMPUAN MOTORIK HALUS PADA ANAK USIA DINI KELOMPOK B4 DI TK ISLAM SULTHONIYAH SAMBAS TAHUN PELAJARAN 2022/2023 - Etria Etria; Parni Parni; Asyruni Multahada (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
The aim of this research is to reveal: 1) Find out the fine motor skills of children in group B4 at the Sulthoniyah Sambas Islamic Kindergarten for the 2022-2023 academic year. 2) Knowing the teacher's strategy for improving fine motor skills in group B4 children at the Sulthoniyah Sambas Islamic Kindergarten for the 2022-2023 academic year. 3) Find out the teacher's evaluation in improving the fine motor skills of children in early childhood group B4 at the Sulthoniyah Sambas Islamic Kindergarten for the 2022-2023 academic year. This research uses a qualitative approach and is a phenomenological type of research. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data reduction, data display, and conclusions. The results of this research show that: 1) Fine motor development in children at the Sulthoniyah Sambas Islamic Kindergarten for the 2022-2023 academic year is developing according to expectations in accordance with standard indicators of children's development achievement levels, namely: drawing according to their ideas; imitate form; carry out exploration with various media and activities; use stationery and cutlery correctly; cut according to the pattern; paste the image precisely; and express yourself through detailed drawing movements. 2) Teacher strategies in developing fine motor skills in children at the Sulthoniyah Sambas Islamic Kindergarten for the 2022-2023 academic year. In implementing learning, teachers use learning strategies in the form of; child-centered learning strategies; learning strategies through play; integrated learning strategies; problem-based learning strategies; and creativity-based learning. 3) Evaluation of teacher strategies in improving fine motor skills in early childhood group B at the Sulthoniyah Sambas Islamic Kindergarten for the 2022-2023 academic year using anecdotal notes and daily checklists which are carried out when the learning process is complete as a form of benchmark in seeing the level of fine motor development in children through teacher strategies in learning activities.